Use of Information Technology in Online Teaching - Martina BOBALOVÁ (Communications of International Proceedings, 2021)
In-class teaching is often combined with distance teaching, or at least supported by the use of information technology. In the current situation, affected by a global pandemic, there is an ever increasing pressure on online and distance teaching, and designing of e-learning courses. Suitable teaching methods to support distance teaching have to be found. Therefore, new support teaching materials for distance and online teaching are being created.
Keywords: Distance learning; e-learning; online teaching